2016
DOI: 10.1017/s0033291716002920
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use is associated with thinner cerebral cortex and larger ventricles in schizophrenia, bipolar disorder and healthy controls

Abstract: The results show a dose-dependent relationship between alcohol use and thinner cortex and ventricular expansion. The findings are present also at lower levels of alcohol consumption and do not differ between schizophrenia or bipolar disorder patients compared to healthy controls. Our results do not support previous findings of increased vulnerability for alcohol-related brain damage in severe mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 106 publications
(151 reference statements)
1
26
0
3
Order By: Relevance
“…A significant strength of our study is the large sample of well characterized and well-matched schizophrenia patients, with only 2 recent studies reaching sample sizes similar to our study (Koenders et al, 2015; Lange et al, 2017). Although the article by Koenders et al is better positioned to address questions regarding the effect of alcohol use on the brain regardless of psychotic disorder diagnosis, our study extends their findings to a large group of individuals with schizophrenia and comorbid alcohol and/or cannabis abuse or dependence.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A significant strength of our study is the large sample of well characterized and well-matched schizophrenia patients, with only 2 recent studies reaching sample sizes similar to our study (Koenders et al, 2015; Lange et al, 2017). Although the article by Koenders et al is better positioned to address questions regarding the effect of alcohol use on the brain regardless of psychotic disorder diagnosis, our study extends their findings to a large group of individuals with schizophrenia and comorbid alcohol and/or cannabis abuse or dependence.…”
Section: Discussionmentioning
confidence: 79%
“…Cannabis use in psychosis patients has been associated with decreased volume in the cingulate cortex (Bangalore et al, 2008; Rapp et al, 2013; Szeszko et al, 2007) and hippocampus (Ebdrup et al, 2010), increased putamen volume (Koenders et al, 2015) or no differences in cannabis users compared to non-users (Cahn et al, 2004; Haller et al, 2013; Malchow et al, 2013b; Solowij et al, 2013; Wobrock et al, 2009). Two early studies examining alcohol use found decreased prefrontal cortex (Mathalon et al, 2003) and cerebellar vermis (Joyal et al, 2004) volume in chronic schizophrenia patients with and without alcohol use disorder, but the majority of studies have found no differences in regional brain volume related to alcohol misuse above and beyond the volume deficits observed in psychosis patients who are non-users (Deshmukh et al, 2005; Gizewski et al, 2013; Lange et al, 2017; Nesvåg et al, 2007; Sullivan et al, 2000; Sullivan et al, 2003; Varnäs et al, 2007). Some of the heterogeneity in region of interest findings can be explained by small sample sizes, differing clinical and demographic characteristics of patient samples, use of alcohol and/or cannabis, severity of substance use, and methods used for volume analysis (VBM vs. automated segmentation vs. manual segmentation).…”
Section: Discussionmentioning
confidence: 99%
“…Light-to-moderate alcohol consumption was associated with adverse brain outcome in our study, and it was similar with the previous studies. Lange et al (2017) adopted brain MR imaging and the Alcohol Use Disorder Identification Test’s consumption part (AUDIT-C) in a study of 609 alcohol consuming adults, and found that higher AUDIT-C scores were linearly associated with thinner cortex in some brain regions. An observational cohort study of 550 participants with weekly alcohol intake and cognitive performance measured repeatedly over 30 years, showed that those drinking moderately had three times the odds of right hippocampal atrophy ( Topiwala et al, 2017 ), which was different with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the addition of TBV as a covariate decreased our power to detect effects, or that adjusted CT values are more sensitive in revealing a relation between striatal DA responses and cortical morphometry. Indeed, there is little consensus as to whether TBV/ICV should [66] or should not [4],[67],[68] be included as a covariate in CT analyses in the context of substance use research. More broadly, there is limited agreement as to how CT should be analyzed (i.e., absolute vs .…”
Section: Discussionmentioning
confidence: 99%